The Role of Teachers in Improving the Ability to Recognize Number Symbols in Children Ages 4-5 years - Lestari Dewi; Noviana Juni; Mufaro’ah (Penerbit Hellow Pustaka, 2024)
This study aims to explore the role of teachers in improving the ability to recognize number symbols in children aged 4-5 years because there are still many children who cannot recognize number symbols 1-10, lack of creativity in children in recognizing number symbols 1-10, lack of curiosity in recognizing number symbols 1-10 and lack of mentioning number symbols 1-10. From the several problems above, the purpose of this study is to find out what are the roles of teachers in improving the ability to recognize number symbols, by using a qualitative descriptive research type, this research technique with data collection used is observation, interviews, documentation. After conducting the research, it can be concluded that: the role of teachers in improving the ability to recognize number symbols in children aged 4-5 years is very important, this can be assessed from: (1). The role of teachers in improving the ability to recognize number symbols is to introduce number symbols 1-10 by teaching the smallest numbers first 1-10. (2) the role of teachers in improving the ability to recognize number symbols by preparing interesting media before the learning process takes place. Inhibiting and supporting factors in increasing the ability to recognize number symbols include: (1) internal factors, factors from the child, (2) external factors, namely family and environment. Family and environment also greatly influence children in increasing their abilities.